PENGENALAN PENGUKURAN KELAYAKAN FINANCIAL PADA UMKM PD PUTRI DI PGC JAKARTA TIMUR - Yusbardini, Yusbardini (Transpublika Publisher, 2023)
The financial feasibility measurement introduction training conducted by the Community Service team had the main objective of providing assistance to PD PUTRI's Small and Medium Enterprises (SMEs) in conducting a comprehensive evaluation of the financial feasibility of their development business. The training process covered several important aspects, including investment and production cost analysis, cost of goods sold, and business feasibility criteria such as Break Even Point (BEP), Net Present Value (NPV), Payback Period (PP), Internal Rate of Return (IRR), and Profitability Index (PI). In addition, in the context of SME development, careful planning requires serious consideration regarding the addition of working capital. The allocation of working capital by SMEs is crucial in providing the technology, equipment, and facilities and infrastructure needed to run the business optimally. Financial feasibility analysis is a key instrument in assessing whether the planned business can provide adequate profits and whether it is economically viable. Within the framework of raising working capital, aspects such as capital utilization efficiency, investment strategy, and risk management are also a key focus. This training aims to equip PD PUTRI's SME team with the knowledge and skills needed to design and evaluate a development strategy based on an in-depth financial feasibility analysis. As a result of the training, PD PUTRI SMEs are expected to make more informed decisions and optimize their working capital management. In addition, it is also expected to improve business competitiveness through a better understanding of the financial factors that influence business viability and sustainability